Is formative assessment a tool for learning for students during PANDEMICS? - A study among first-phase students of a medical school in North India - Gesu Singla; Bharti Singla; Shweta Singla; Hitashi Bansal (Wolters Kluwer Medknow Publications, 2023)
Introduction: COVID pandemic has shifted the teaching of students from on site to online mode. Initially, it was difficult for the students as well as teachers to acclimatize to this system of education but with the passage of time, this system has imbibed into everyone's life. The feedback given in online formative assessment has proved to be really useful for the students in improving their performance. Materials and Methods: Online oral formative assessment was taken during online classes which were being conducted on the Zoom platform. Later on, students' feedback was taken using a questionnaire created in the form of Google Forms. Results: Students appreciated this method of online oral formative assessment as well as detailed feedback. Furthermore, exposure to multiple questions and answers was altogether beneficial for all. Although there were technical problems like network connectivity which were faced by few students. Conclusions: In lieu of the further waves of the pandemic, if the online mode of education will continue then this method of oral online formative assessment can be a very useful and time-saving method.